Dysregulation of the immune response in TGF-β signalopathies - Rodari, Marco M.; Cerf-Bensussan, Nadine; Parlato, Marianna (Frontiers in Immunology, 2022)
The TGF-β family of cytokines exerts pleiotropic functions during embryonic development, tissue homeostasis and repair as well as within the immune system. Single gene defects in individual component of this signaling machinery cause defined Mendelian diseases associated with aberrant activation of TGF-β signaling, ultimately leading to impaired development, immune responses or both. Gene defects that affect members of the TGF-β cytokine family result in more restricted phenotypes, while those affecting downstream components of the signaling machinery induce broader defects. These rare disorders, also known as TGF-β signalopathies, provide the unique opportunity to improve our understanding of the role and the relevance of the TGF-β signaling in the human immune system. Here, we summarize this elaborate signaling pathway, review the diverse clinical presentations and immunological phenotypes observed in these patients and discuss the phenotypic overlap between humans and mice genetically deficient for individual components of the TGF-β signaling cascade.